2007
DOI: 10.1080/09637480701359149
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different coloured carrot cultivars on antioxidative capacity based on their carotenoid and phenolic contents

Abstract: We compared five new carrot cultivars with a conventional cultivar in consideration of their content of carotenoids, phenolics and according antioxidative capacity. We chose the following cultivars: orange, white, yellow, red, solid-coloured purple and purple with an orange core. Examinations were conducted over two cultivation periods (2003 and 2004). The white, yellow and solid-coloured purple cultivars showed quite low contents of carotenoids, but the solid-coloured purple contained most phenolic compounds.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 30 publications
(34 reference statements)
7
46
1
1
Order By: Relevance
“…The results obtained are congruent with the report that antioxidant capacity of hydrophilic extracts of carrot roots correlated with the total phenol content [33]. Chlorogenic acid, total phenols and total anthocyanins significantly correlated with total antioxidant capacity measured using DPPH and ABTS methods in hydrophilic phase extracts from root of different colors [3].…”
Section: Resultssupporting
confidence: 89%
“…The results obtained are congruent with the report that antioxidant capacity of hydrophilic extracts of carrot roots correlated with the total phenol content [33]. Chlorogenic acid, total phenols and total anthocyanins significantly correlated with total antioxidant capacity measured using DPPH and ABTS methods in hydrophilic phase extracts from root of different colors [3].…”
Section: Resultssupporting
confidence: 89%
“…Papers reporting the antioxidant activity of foods in relation to these compounds are much fewer and the results lack coherence. Although some papers reported that carotenoids contributed to the antioxidant activity of foods (Arnao et al, 2001;Dewanto et al, 2002;Di Vaio et al, 2008;Gliszczyń ska-Ś wigło et al, 2006;Grassmann et al, 2007;Sá nchezMoreno et al, 2003;Zanfini et al, 2010), in others no correlation was found between the carotenoid content and the antioxidant capacity (Ancos et al, 2002;Choi et al, 2007;Lavelli et al, 2009) or the antioxidant contribution of carotenoids was negligible (Gardner et al, 2000) or lower than those of phenolic compounds (Gil et al, 2002) or vitamin C (Valle et al, 2007).…”
Section: Antioxidant Activity Of Food Carotenoidsmentioning
confidence: 95%
“…However, by using porcine endothelial cells, Metzger et al (2008) demonstrated that the antiinflammatory activity of purple carrots was due to polyacetylene compounds rather than anthocyanins. A recent study compared different varieties of carrots and found that the white, yellow and purple varieties had a low content of carotenoids, while the purple variety contained the highest level of phenolic compounds (Grassmann et al 2007). Only the red-pigmented varieties contained lycopene.…”
Section: Nutritional and Health Promoting Indicatorsmentioning
confidence: 97%